Q: What is the quadratic formula of 6x2 11x-35 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.

In the absence of a proper statement of the equation I can only guess at answers. How about (2x + 3)(3x - 5) which is the factorisation of 6x2 - x - 15 = 0? In which case x = -2/3 or 5/3.

Taking the equation to be y=ax2 + bx +c , and using the formula x = -b plus/minus sqrt (b2-4ac), all over 2a: x = (-3+21)/12 or (-3-21)/12 so x = 1.5 or -2

6x2

the equation 6x^2 - 4x + 25 is a quadratic equation due to the 6x^2 term. Whatever number on the x squared term changes it to a quadratic equation if you were to get rid of the 6x^2 then the equation would simply be -4x+25 making it simply a linear equation. when ever you have an x raised to 2 that term is the quadratic term in the equation.

Related questions

10

In the absence of a proper statement of the equation I can only guess at answers. How about (2x + 3)(3x - 5) which is the factorisation of 6x2 - x - 15 = 0? In which case x = -2/3 or 5/3.

First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.First step should be to take everything to the left side:6x2 - 18x - 12 = 0Next you might divide by the common factor, 6:x2 - 3x - 2 = 0It seems you have to use the quadratic formula for this one. Use a = 1, b = -3, c = -2.

Taking the equation to be y=ax2 + bx +c , and using the formula x = -b plus/minus sqrt (b2-4ac), all over 2a: x = (-3+21)/12 or (-3-21)/12 so x = 1.5 or -2

6x2

Solve the following equation for x by using the quadratic formula. (there might be more than one solution 6x2 + 2x - 3 = 0

6x2 is a multiplication operation that equals 12. It does not have a unit of measurement such as meters.

the equation 6x^2 - 4x + 25 is a quadratic equation due to the 6x^2 term. Whatever number on the x squared term changes it to a quadratic equation if you were to get rid of the 6x^2 then the equation would simply be -4x+25 making it simply a linear equation. when ever you have an x raised to 2 that term is the quadratic term in the equation.

10x2 - 56 = 88 - 6x2 : 10x2 + 6x2 = 88 + 56 : 16x2 = 144 : x2 = 9 : x = ± 3

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: (-1 plus or minus the square root of 265) divided by 12 x = 1.2732350496749756 x = -1.439901716341642

The factors of 6x2+7x-5 are (3x+5) and (2x-1).

10x2 - 64 = 36 + 6x2; whence, 4x2 - 100 = 0, x2 = 25, and x = ±5.